Legal Consequences of the Issuance of Government Regulation in Lieu of Law Number 2 of 2022 on the Legal Politics in Indonesia - Abdul Hamid Sobri; Iza Rumesten RS; Suci Flambonita (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
The issuance of Perppu Number 2 of 2022 has led to various dynamic debates within society. The government's actions have shown attempts to